EVALUASI USAHA PENGGILINGAN PADI SUMBER HIDUP DI DESA MARINDI KECAMATAN HARUAI KABUPATEN TABALONG - Marliani, Gusti (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2016)
The purpose of this research is to determine the production cost, the eligibility and sensitivity of â€œSumber Hidupâ€ rice milling business in Marindi village, sub-district of Haruai, Tabalong regency. This research uses quantitative analysis methods. The data collecting has been done in April to May 2015. The quatitative analysis methods use invesment criteria analysing with:, Net Present Value (NPV) , Internal Rate of Return (IRR), Net Benefit Cost Ratio (Net B/C), and business sensitivity. Based on the research, the eligibility of business study conclude that â€œSumber hidupâ€ rise milling business is worth to be carried on as long as the range of production cost is 10% to 40%. But if the production cost reach more than 50% of the whole cost, the business is not worth to be carried on.